The Relevance Of Farmers' Socio-Economic Conditions In Decision Making In Integrated Crops-Livestock Patterns In Pringgabaya District, East Lombok Regency - Dudi Septiadi; Umbu Joka; Yudhistira Ardana (Fakultas Pertanian, Universitas Timor, 2022)
Integrated crops-livestock systems is a farming concept that consists of several subsystems. One subsystem with another subsystem has a mutualism symbiotic relationship, where each subsystem benefits from each other. The purpose of this study was to analyze the socio-economic factors of farmers that influence farmers' decision making in using an integrated farming pattern that produces optimally. The research method was a quantitative approach with multiple regression analysis. Determination of research respondents was done by